(untitled) (Latakia University Journal -Medical Sciences Series, 2021)
Aim of the Study: This study aimed to evaluate the microleakage in the interface surface between glass ionomer cement types (conventional, metal-reinforced, resine-modified) and both Composite Resine and gingival wall in class II open sandwich technique restorations. Materials & methods: 36 upper first premolars were collected. Two class II cavities with specific dimensions had prepared on each tooth mesially and distally and distributed into three groups every group includes 12 tooth and the cavities Prepared according "open sandwich" technique were restorated using conventional glass ionomer cement (Ionofill Plus) and metal-reinforced (Argion) and resin-modified (Vitremer) and the restoration was completed with composite resine (Tetric Cream HB). Results: There is a statisticed difference of microleakage’s results between three types of glass ionomer cement and both composite resine and gingival wall although the lowest leakage rate was by adopting resin-modified glass ionomer cement while the highest leakage rate was by adopting metal reinforced glass ionomer cement.